PENDEKATAN MAKROSASTRA DALAM KONSEP INIMITABILITAS AL-QUR’AN: TELAAH PEMIKIRAN NASR HAMID ABU ZAID - Nuril Hidayah (LPPM STAI Muhammadiyah Probolinggo, 2018)
This study is aimed at identifying Abu>-Zayd’s position with his theory of i’ja>z al-Qur’an among another theoretician of i’ja>z lugawi> and his contribution toward i’ja>z discourse and qur’anic studies. To achieve that goal, it will explore some elements underlying his theory, namely the basic element, the mode of thought, the essential element, the aim and the end of his i’ja>z thought.